Somatization in dermatology - George W. M. Millington; Morinola T. Shobajo; James Wall; Mohammad Jafferany (Wiley, 2022)
Abstract Medically unexplained dermatologic symptoms, such as pruritus, numbness and burning are known as somatization. These cutaneous symptoms can be very difficult to treat because of an absence of an objective explanation and they may not fit neatly into any known dermatological or psychiatric condition. These disorders are more commonly encountered in primary care and in dermatology, rather than in psychiatry. Certain skin disorders, for example, pruritus, could be a manifestation of somatization and others may predispose to somatic symptoms, for example, atopic dermatitis and psoriasis. Although there has been increasing research in the interconnection between psychiatry and dermatology, psychodermatology is a relatively new crossover discipline in clinical practice and recognition of psychodermatological conditions, such as cutaneous somatic disorders, can be difficult. Somatization may occur with or without the existence of a dermatological disease. When a dermatological disorder is present, somatization should be considered when the patient is worrying too much about their skin, spending too much time and energy on it and especially if the patient also complains of many non‐cutaneous symptoms. Purely cutaneous somatic conditions include for example, the genital pain syndromes or Gardner-Diamond syndrome, characterized by unexplained bruising, which usually affects women. Effective management tools may include mindfulness therapies, pharmacotherapy with selective serotonin reuptake inhibitors, tricyclic antidepressants and cognitive conduct therapy. Electroconvulsive therapy can also be considered in extremely rare cases for treatment of severe somatization on a background of mood disorders. This paper discusses somatization, its relationship to immunodermatoses and its relevance to clinical practice.